On the Alber equation for shoaling water waves. (25th November 2021) - Kluczek, Mateusz; Andrade, David; Stiassnie, Michael
Abstract: Abstract : The problem of unidirectional shoaling of a water-wave field with a narrow energy spectrum is treated by using a new Alber equation. The stability of the linear stationary solution to small non-stationary disturbances is analysed; and numerical solutions for its subsequent long-distance evolution are presented. The results quantify the physics which causes the gradual decay in the probability of freak-wave occurrence, when moving from deep to shallow coastal waters.